Allele‐specific silencing therapy for Dynamin 2‐related dominant centronuclear myopathy. Issue 2 (15th December 2017) - Trochet, Delphine; Prudhon, Bernard; Beuvin, Maud; Peccate, Cécile; Lorain, Stéphanie; Julien, Laura; Benkhelifa‐Ziyyat, Sofia; Rabai, Aymen; Mamchaoui, Kamel; Ferry, Arnaud; Laporte, Jocelyn; Guicheney, Pascale; et al.
Abstract: Rapid advances in allele‐specific silencing by RNA interference established a strategy of choice to cure dominant inherited diseases by targeting mutant alleles. We used this strategy for autosomal‐dominant centronuclear myopathy (CNM), a rare neuromuscular disorder without available treatment due to heterozygous mutations in the DNM2 gene encoding Dynamin 2. Allele‐specific siRNA sequences were developed in order to specifically knock down the human and murine DNM2 ‐mRNA harbouring the p.R465W mutation without affecting the wild‐type allele. Functional restoration was achieved in muscle from a knock‐in mouse model and in patient‐derived fibroblasts, both expressing the most frequently encountered mutation in patients. Restoring either muscle force in a CNM mouse model or DNM2 function in patient‐derived cells is an essential breakthrough towards future gene‐based therapy for dominant centronuclear myopathy. Synopsis: Autosomal dominant centronuclear myopathy (AD‐CNM) is a rare congenital myopathy due to heterozygous mutations in the DNM2 gene encoding Dynamin 2. Allele‐specific silencing of the mutant allele alleviates the phenotype in a CNM knock‐in mouse model and patient‐derived fibroblasts. siRNA targeting the mutant allele leads to functional restoration of the impaired endocytosis in mutant human fibroblasts. Early intra‐muscular administration of AAV1 expressing allele‐specific shRNA prevents the disease in the mouse model. Late treatment in the disease's time course partially improve the phenotype due to a weaker transduction capacity of the muscle. Allele‐specific silencing is a promising therapeutic strategy for AD‐CNM. Abstract : Autosomal dominant centronuclear myopathy (AD‐CNM) is a rare congenital myopathy due to heterozygous mutations in the DNM2 gene encoding Dynamin 2. Allele‐specific silencing of the mutant allele alleviates the phenotype in a CNM knock‐in mouse model and patient‐derived fibroblasts.